1989
DOI: 10.1161/01.str.20.11.1449
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-induced thrombocytopenia.

Abstract: There are two types of heparin-induced thrombocytopenia. Type I is more common, has an early onset, and is mild, transient, and benign. Type I is due to direct heparin-induced platelet aggregation and is rarely associated with thromboembolic sequela. Type II is infrequent, has a late onset, and is more severe. Type II is due to an immune-mediated platelet aggregation caused by IgG and IgM that becomes bound to platelets. In Type II, the antibody titers decline over several months; however, early reexposure can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(11 citation statements)
references
References 130 publications
0
10
0
1
Order By: Relevance
“…22 Subsequent in vitro studies have demonstrated no difference. 23 Although an increased number of heparin exposures does not significantly increase the risk of developing HIT II, it may, as with other forms of drug-induced thrombocytopenia, contribute to an earlier onset after repeat administration.24…”
Section: Discussionmentioning
confidence: 99%
“…22 Subsequent in vitro studies have demonstrated no difference. 23 Although an increased number of heparin exposures does not significantly increase the risk of developing HIT II, it may, as with other forms of drug-induced thrombocytopenia, contribute to an earlier onset after repeat administration.24…”
Section: Discussionmentioning
confidence: 99%
“…On the eleventh day of heparin treatment, her platelet count dropped from 521,000/mm 3 to 50,000/ mm 3 . On the same day, she became disoriented and lethargic, without focal abnormalities.…”
Section: Case Reportmentioning
confidence: 94%
“…On admission in May of 1988, her temperature was 37.3° C. Her erythrocyte count was 5.3x 10 6 /mm 3 , her leukocyte count was 17,500/mm 3 , and her platelet count was 687,000/mm 3 . Her hemoglobin concentration was 13.6 g/100 ml, and her hematocrit was 41%.…”
Section: Case Reportmentioning
confidence: 98%
See 1 more Smart Citation
“…"white clot syndrome". Während nachweisbare Anti-PF-4-Antikörper oder der positive HIPA-Test die Diagnose bestätigen, gibt es bislang keinen Test, der die HIT Typ II mit 100%iger Sicherheit ausschließen kann [2,3]. Wenn beide Tests negativ sind, ist eine HIT Typ II aber unwahrscheinlich.…”
Section: Heparininduzierte Thrombozytopenieunclassified